Four-wave mixing analyses for future ultra fast wavelength conversion at 0.64 Tb∕s in a semiconductor optical amplifier - Kharraz, Osayd M.; Ahmad, Harith; Forsyth, David I.; Dernaika, Mohamad; Mohammad, Abu Bakar; Zulkifli, Mohd Zamani; Ismail, Mohd Faizal; Mohd Supa’at, Abu Sahmah (SPIE, 2014)
This paper describes numerical and analytical analyses relating to the use of nonlinear four-wave mixing in a semiconductor optical amplifier medium for anticipated wavelength conversion at ultrahigh data rates of 320 and 640 Gb∕s. The proposed system guidelines and design show that a maximum wavelength shift of 30 nm can be achieved at 640 Gb∕s, while still maintaining an acceptable bit error rate. In addition, the impact of the pump–probe ratio and semiconductor optical amplifier bias current are investigated and the results are reported. © 2014 Society of Photo-Optical Instrumentation Engineers (SPIE) [DOI: 10.1117/1.OE.53.11.116111]